Targeting Mitochondrial Metabolism in Neuroinflammation: Towards a Therapy for Progressive Multiple Sclerosis. Issue 10 (October 2018) - Peruzzotti-Jametti, Luca; Pluchino, Stefano
Abstract : The lack of effective treatment options for chronic neurological conditions, such as multiple sclerosis (MS), highlights the need to re-evaluate disease pathophysiology in the process of identifying novel therapeutic targets. The persistent activation of mononuclear phagocytes (MPs) is one of the major drivers of neurodegeneration and it sustains central nervous system (CNS) damage. Mitochondrial metabolism influences the activity of MPs, and the metabolites that they produce have key signalling roles in inflammation. However, how changes in immune cell metabolism sustain a chronic state of neuroinflammation is not fully understood. Novel molecular and cellular therapies for chronic neuroinflammation should be developed to target mitochondrial metabolism in innate immune cells to prevent secondary neurological damage and the accumulation of irreversible disability in patients. Highlights: MPs, including resident microglia and blood-borne macrophages, control local immune surveillance in the CNS. In chronic neurological conditions, such as MS, MPs are persistently activated and responsible for several maladaptive responses that include neurotoxicity and inhibition of remyelination. Cell metabolism guides the activation of MPs towards a proinflammatory or anti-inflammatory phenotype and function, depending on the local microenvironment. Specific metabolites act as intracellular and extracellular signalling molecules regulating neuroimmune interactions and inflammation. Neural stem cells interfere with MP metabolism via selective uptake of specific metabolites and secretion of metabolic enzymes packed into extracellular vesicles.